2019
DOI: 10.1111/jcmm.14390
|View full text |Cite
|
Sign up to set email alerts
|

The exploration of mechanisms of comorbidity between migraine and depression

Abstract: Migraine comorbid with depression is common and is often encountered in clinical practice. The comorbidity may lead to more serious conditions with other symptoms and a longer duration of treatment and it may impose heavy economic and social burdens, directly or indirectly, on patients and their families. Numerous studies have been published on the association of migraine with depression. Numerous literature have showed that the comorbidity may have a common complicated pathogenic mechanism involving biopsycho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
71
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(79 citation statements)
references
References 91 publications
(294 reference statements)
1
71
0
7
Order By: Relevance
“…The relationship between cerebral cortex thickness and cerebral activity needs further exploration to understand the co-pathogenic relationship between patients' cerebral function who was having depression with migraines [37][38]. The comorbid condition of depressive and migraine patients exhibits a marked decrease in the intrinsic brain activity in the thalamus [39]. Another study determined that some older people who do not have dementia but have a migraine and MDD had an overall reduced total brain volume as well as gray and white matter compared to patients who presented with either of the diseases [40].…”
Section: Morphological Changes In Cerebral Cortex and Thalamusmentioning
confidence: 99%
“…The relationship between cerebral cortex thickness and cerebral activity needs further exploration to understand the co-pathogenic relationship between patients' cerebral function who was having depression with migraines [37][38]. The comorbid condition of depressive and migraine patients exhibits a marked decrease in the intrinsic brain activity in the thalamus [39]. Another study determined that some older people who do not have dementia but have a migraine and MDD had an overall reduced total brain volume as well as gray and white matter compared to patients who presented with either of the diseases [40].…”
Section: Morphological Changes In Cerebral Cortex and Thalamusmentioning
confidence: 99%
“…Migraine is a widespread neurovascular disabling disorder affecting up to 15% of the worldwide population and is typically characterized by one-sided throbbing long-lasting moderate or severe pain [ 1 , 2 ]. Migraine is associated with multiple psychiatric comorbidities such as anxiety, depression and panic disorders [ 3 , 4 , 5 , 6 ]. Despite this clear association, the CNS neuronal centers underlying the link between migraine and the comorbid psychiatric conditions remains to be determined.…”
Section: Introductionmentioning
confidence: 99%
“… 4 Multiple studies have demonstrated that the comorbidity of migraine and depression is bi-directional 4 , 5 ; therefore, various shared etiologic mechanisms associated with depression and migraine have been proposed. 6 , 7 While no single possibility has provided sufficient clarification, a dysfunctional serotoninergic system could be an explanation. 7 9 …”
Section: Introductionmentioning
confidence: 99%
“… 6 , 7 While no single possibility has provided sufficient clarification, a dysfunctional serotoninergic system could be an explanation. 7 9 …”
Section: Introductionmentioning
confidence: 99%